Genetic variants within the COL5A1 gene are associated with ligament injuries in physically active populations from Australia, South Africa, and Japan. Issue 2 (1st February 2023) - Alvarez-Romero, Javier; Laguette, Mary-Jessica N.; Seale, Kirsten; Jacques, Macsue; Voisin, Sarah; Hiam, Danielle; Feller, Julian A.; Tirosh, Oren; Miyamoto-Mikami, Eri; Kumagai, Hiroshi; Kikuchi, Naoki; Kamiya, Nobuhiro; et al.
ABSTRACT: Previous small-scale studies have shown an association between the COL5A1 gene and anterior cruciate ligament (ACL) injury risk. In this larger study, the genotype and allele frequency distributions of the COL5A1 rs12722 C/T and rs10628678 AGGG/deletion (AGGG/-) indel variants were compared between participants: (i) with ACL injury in independent and combined cohorts from South-Africa (SA) and Australia (AUS) vs controls (CON), and (ii) with any ligament (ALL) or only ACL injury in a Japanese (JPN) cohort vs CON. Samples were collected from SA (235 cases; 232 controls), AUS (362 cases; 80 controls) and JPN (500 cases; 1, 403 controls). Genomic DNA was extracted and genotyped. Distributions were compared, and inferred haplotype analyses performed. No independent associations were noted for rs12722 or rs10628678 when the combined SA + AUS cohort was analysed. However, the C-deletion (rs12722-rs10628678) inferred haplotype was under-represented ( p = 0.040, OR = 0.15, CI = 0.04-0.56), while the T-deletion inferred haplotype was over-represented in the female SA + AUS ACL participants versus controls ( p < 0.001, OR = 4.74, CI = 1.66-13.55). Additionally, the rs12722 C/C genotype was under-represented in JPN CON vs ACL ( p = 0.039, OR = 0.52, 0.27-1.00), while the rs10628678 −/− genotype was associated with increased risk of any ligament injuries ( p = 0.035, OR = 1.31, CI = 1.02-1.68) in the JPN cohort. Collectively, these results highlight that a region within the COL5A1 3'-UTR is associated with ligament injury risk. This must be evaluated in larger cohorts and its functional relevance to the structure and capacity of ligaments and joint biomechanics be explored. Highlights The COL5A1 T-deletion inferred haplotype (rs12722-rs10628678) was associated with an increased risk of ACL rupture in the combined SA and AUS female participants. The COL5A1 C-deletion inferred haplotype (rs12722-rs10628678) was associated with a decreased risk of ACL rupture in the combined SA and AUS female participants. The COL5A1 rs12722 C/C and rs10628678 −/− genotypes were associated with increased risk of ACL rupture and of ligament injuries in JPN, respectively. A region within the COL5A1 3'-UTR is associated with risk of ligament injury, including ACL rupture, and therefore the functional significance of this region on ligament capacity and joint biomechanics requires further exploration.